ROLE OF HEPCIDIN IN MECHANISM OF ANEMIA CHRONIC DISEASE PATIENTS - Suega, Ketut (BALI MEDICAL JOURNAL, 2014)
Background: Anemia chronic disease (ACD) is an anemia found in certain chronic disease states, typically marked by the disturbance of iron homeostasis or hypoferremia. This condition leads to shortage of iron for hemoglobin synthesis but the iron storage in bone marrow is left undisturbed. The discovery of hepcidin and its role in iron metabolism has given new insights in anemia chronic disease management. Consecutive sampling method was applied to choose ACD patients at Sanglah General Hospital, Bali-Indonesia. Questionnaire was constructed to note demographic aspect and disease or clinical condition underlies ACD (inflammation, infection, malignancy and others). Hepcidin, Serum IL-6 and CRP level were measured. Sample size and Path analysis mediation method were used to define hepcidin’s role on mechanism how anemia develop in ACD patients in which the direct and indirect effects of IL-6 and CRP to hemoglobin (Hb) were counted partially or combined through hepcidin mediation variable. The cumulative influence of IL-6, CRP and hepcidin on anemia (Hb) was only 0.12 or about 12% of hemoglobin level was influenced by IL-6, CRP and hepcidin together whereas the other 93% was influenced by another unknown and unclear factors. Hepcidin could be used as a mediation variable for the development of anemia because the direct influence of IL-6 as exogenous factor was less than its indirect influence through hepcidin. It was not proven for CRP as exogenous variable because the direct influence of CRP to hemoglobin was stronger than the influence of CRP through hepcidin.